Accounting and Sustainability Practices grounded in Spirituality and Ethics - Ermawati, Yana; Suhardianto, Novrys (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2024)
This study investigates the potential impact of spirituality and ethics, particularly within the Islamic religion on advancing sustainable accounting principles and reevaluating the modern capitalist paradigm. This study aims to demonstrate integrating spiritual and ethical principles into accounting methods to enhance transparency, fairness, and accountability. It will achieve this through examining case studies and an extensive review of relevant literature. Moreover, the study assesses how this method might facilitate the shift towards a more sustainable paradigm, wherein corporations prioritize financial gain and the societal and ecological consequences of their activities. Incorporating spiritual principles into accounting methods involves integrating these values into the decision-making process, which will have a long-term impact on the organization. Adopting these principles enables companies to meet regulatory requirements, improve operational effectiveness, and generate additional benefits for all stakeholders, including shareholders, employees, communities, and the environment.